From the Wastewater Treatment Plant to the Turnstiles of Urban Water and District Heating Networks - Gruber-Glatzl, Wolfgang; Brunner, Christoph; Meitz, Sarah; Schnitzer, Hans (Frontiers in Sustainable Cities, 2020)
Wastewater treatment plants (WWTP) are among the largest energy consumers in municipalities and cause high operating costs. At the same time, many WWTPs produce biogas and have immense untapped potential for the integration of heat pumps (HP). District heating operators are looking for new possibilities to diversify their heat production portfolio and to provide cheap and clean heat to their customers. In our work, we investigate the case study of the WWTP Gleisdorf (Austria) and propose a combination of biogas utilization and heat pump integration to deliver heat for all internal thermal processes as well as to a 1000 m heat connection line (HCL) towards the district heating network. The net annual costs of different scenarios were calculated for economic comparison. Negative net annual costs mean net annual savings. The reference scenario (biogas combined heat and power, no HCL, no HP; net annual costs of 51,000 €/year) is compared with 3 different heat pump integration options (HP-IO). The HP IOs are considering different hydraulic connections, flow temperatures and heat exchanger placement. The HP-IO-1 focuses on the low-temperature internal demands, but proves to be too limited to balance out the high cost of the HCL. HP-IO-2 operates at higher temperatures (75 °C) leading to the lowest efficiency, but ultimately achieving the lowest net annual costs (-57,700 €/year with a 750 kWth HP). HP-IO-3 uses a serial heating concept trying to take advantage of lower flow temperatures while also delivering heat to the district heating network. At 300-400 kWth this leads to net annual costs of -50,100 €/year. The price ratio of 0.5 (40 €/MWh selling price of heat to 80 €/MWh purchasing price of electricity) are varied to analyze the sensitivity of the results. HPs already play an increasing role in the district heating sector, using sewage water as a heat source. The combined analysis of biogas utilization, HP integration options and the thermal as well as electrical demands of WWTP and district heating networks allow the determination of the most viable option.